Patients as teachers: a randomised controlled trial on the use of personal stories of harm to raise awareness of patient safety for doctors in training. Issue 1 (18th August 2014) - Jha, Vikram; Buckley, Hannah; Gabe, Rhian; Kanaan, Mona; Lawton, Rebecca; Melville, Colin; Quinton, Naomi; Symons, Jools; Thompson, Zoe; Watt, Ian; Wright, John
Abstract : Background: Patient safety training often provides learners with a health professional's perspective rather than the patient's. Personal narratives of health-related harm allow patients to share their stories with health professionals to influence clinical behaviour by rousing emotions and improving attitudes to safety. Aim: This study measured the impact of patient narratives used to train junior doctors in patient safety. Methods: An open, multi-centre, two-arm, parallel design randomised controlled trial was conducted in the North Yorkshire East Coast Foundation School (NYECFS). The intervention consisted of 1-h-long patient narratives followed by discussion. The control arm received conventional faculty-delivered teaching. The Attitude to Patient Safety Questionnaire (APSQ) and the Positive and Negative Affect Schedule (PANAS) were used to measure the impact of the intervention. Results: 142 trainees received the intervention; 141 the control teaching. There was no evidence of a difference in post-intervention APSQ scores between the groups. There was a statistically significant difference in the underlying distribution of both post PA (positive affect) and post NA (negative affect) scores between the groups on the PANAS (p<0.001) with indications of both higher PA and NA scores in the intervention group. Conclusions: Involving patients with experiences of safety incidents in training has an ideological appeal and seems an obvious choice in designing safety interventions. On the basis of our primary outcome measure, we were unable to demonstrate effectiveness of the intervention in changing general attitudes to safety compared to control. While the intervention may impact on emotional engagement and learning about communication, we remain uncertain whether this will translate into improved behaviours in the clinical context or indeed if there are any negative effects. Trial registration number: Grant reference no. RP-PG-0108-10049.